Desempenho das empresas citadas na Operação Lava Jato sob a ótica das Teorias da Graxa e Areia Sobre Rodas - Ataides, Camila Moraes de (2020)
Corruption is a social, political and economic phenomenon that affects many nations. In view of the important effects that it can cause on the economy of countries, on the performance of companies and society as a whole, researchers of different nationalities use it as an object of investigation. Under a common view, corruption is considered harmful in the face of inequalities and inefficient allocation of resources that it can cause, however the researchers sought to evaluate it from another perspective, in which is considers it to be beneficial for economic activity, in view of the possibility of overcoming barriers present in environments with fragile institutional structures, such as the slowness and inefficiency of public services, high bureaucracy, high tax burden, among other characteristics that hinder the performance of companies in the market. In this context the Grease on the Wheels Theory and Sand on th Wheels Theory are presented, on which they discuss, in an opposite way, the effects of corruption on the economies of countries and on the performance of companies. This study sought to verify and analyze the effect of corrupt practices on the performance of Brazilian companies mentioned in Operation Lava Jato. The sample has 12 (twelve) public companies mentioned in Operation Lava Jato, and Tobin's q was adopted as a performance measure. For statistical tests, descriptive statistics and averages tests were applied to analyze the variation of Tobin's q over the years. In addition, a multiple linear regression test was applied with the Tobin's q and other independent and control variables in order to verify the differences in the performance of state and private companies. The main conclusions of the study are: (i) the companies mentioned in corruption scandals, most of them, showed an improvement in their performance over the years; (ii) the majority of companies cited in corruption scandals performed better, compared to similar companies not cited in any case of fraud and corruption; and, (iii) the state companies cited in corruption scandals have not benefited as much as the private companies cited.